ALAT PENGERING SURYA TANPA LISTRIK (APKOSTRIK) UNTUK UMKM KERUPUK DI DESA BRABO - Firdaus, Rifki; Annanto, Gilar Pandu; Wibowo, Bayu Siswo (Program Kreativitas Mahasiswa - Teknologi, 2014)
Kerupuk is one of complementary food almost in all Indonesiaâs food. Kerupuk has function to increase taste because its delicious and consist of many variation. On of kerupuk producen is Mrs.Muayanah. Mrs.Muayanah has produced kerupuk for ten years. However, her business is stagnant because limited stuffs and her stuffs still simple so canât produce in big number especially drying process which take longest time of all production process. From that description, we try to give solution designing solar oven to increase kerupuk productivity. APKOSTRIK is dryer which use solar and reflect it to the object (kerupuk) to help drying process by using solar collector. By reflecting and focusing solar sun, it will increase received hot energy till maximal and less time needed. Another that, solar also absosrbed by copper plate and temperature will keep increasing because copper plate absorb hot energy from direct solar and reflected one to increase drying speed. Room also affect drying process because room is isolated by alumunium. This simple functional oven can help increasing kerupuk productivity and profit because without any complicated knowledge or experiences everyone can use it. This oven also need not any electricity and production cost so low economic citizen or micro business can be prosperous especially in kerupuk business.Keywords : Drying, Kerupuk, Solar Collector, Without electricity